2017
DOI: 10.1016/j.cemconcomp.2016.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the drying shrinkage performance of alkali-activated slag mortars

Abstract: In this work, drying shrinkage of four alkali-activated slag (AAS) mortars, prepared using various types/dosages of activator, was characterized at four different levels of relative humidity (RH) and two drying regimes (i.e. direct and step-wise drying). The results show that drying shrinkage values of AAS are significantly dependent on the drying rate, as AAS shrinks more when the RH is decreased gradually instead of directly. At high RH, the drying shrinkage of AAS exhibits a considerable visco-elastic/visco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
66
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 208 publications
(74 citation statements)
references
References 32 publications
7
66
1
Order By: Relevance
“…Němeček et al (2011) argue that AAM have an inherent modulus of elasticity in a range between 17 and 18 GPa and that this property appears to be, for a given formulation, independent of the precursor material or the type of curing regime employed. Ye et al (2017) produced blast furnace slag based AAM with modulus of elasticity varying between 13.25 and 20.71 GPa.…”
Section: Compressive Strength and Modulus Of Elasticitymentioning
confidence: 99%
“…Němeček et al (2011) argue that AAM have an inherent modulus of elasticity in a range between 17 and 18 GPa and that this property appears to be, for a given formulation, independent of the precursor material or the type of curing regime employed. Ye et al (2017) produced blast furnace slag based AAM with modulus of elasticity varying between 13.25 and 20.71 GPa.…”
Section: Compressive Strength and Modulus Of Elasticitymentioning
confidence: 99%
“…increased shrinkage magnitude but reduced shrinkage kinetics) of alkaliactivated slag (AAS) to the alkali incorporation in the main hydrated product, i.e. calcium-alumina-silicatehydrate (C-A-S-H) (Ye and Radlińska 2016c;Ye et al 2017a).…”
Section: Introductionmentioning
confidence: 99%
“…One of the shortcomings is that AAS is susceptible to shrinkage and microcracks [29][30][31][32]. Several studies have revealed AAS concrete has higher drying shrinkage than OPC concrete [31,[33][34][35][36][37][38][39][40]. For example, Palacios and Puertas [32] measured the drying shrinkage of waterglass-activated slag mortars.…”
Section: Introductionmentioning
confidence: 99%